Leading Sectors and Economic Structure of Luwu Timur District - Umar Umar (Trunojoyo University of Madura, 2022)
This research was conducted in East Luwu District, South Sulawesi Province. The data used secondary data sourced from the Central Statistics Agency (CSA). The research method uses Location Quotient and shift-share analysis techniques. The results showed two leading sectors in East Luwu Regency with a value of LQ more than 1, namely the Agriculture, Forestry, and Fisheries Sectors and the Mining and Quarrying Sector. Based on the results of shift-share analysis, the values of dij and mij of all sectors are positive. This shows that all industries in East Luwu Regency have shifted from their reference areas and greatly influence the shift of industries in East Luwu Regency and have relatively fast growth. In addition, nine sectors have a competitive advantage with a positive cij value and eight sectors that do not have a competitive advantage with a negative cij value.